Implementation of Criminal Sanctions against Perpetrators of Theft in Indonesia - Samsidar Samsidar (Journal of Strafvordering Indonesian, 2024)
Theft is one of the most common forms of crime in society and has been strictly regulated in the Criminal Code (KUHP). Law enforcement against perpetrators of theft plays an important role in creating a sense of security and justice. This article aims to analyze how criminal sanctions are applied to perpetrators of theft in Indonesia, by reviewing the applicable legal basis, law enforcement practices, and challenges in its implementation. This study uses a normative legal approach with literature study as the main method. The results of the study indicate that although the legal provisions are quite adequate, there are still challenges in the judicial process, including differences in judges' interpretations, the socio-economic conditions of the perpetrators, and the effectiveness of sanctions in providing a deterrent effect. The discussion also touches on the importance of criminal policy reform and the need for a rehabilitative approach for certain perpetrators. Thus, law enforcement against theft must be carried out proportionally and fairly.